2008
DOI: 10.1002/bem.20417
|View full text |Cite
|
Sign up to set email alerts
|

Statistical analysis of personal radiofrequency electromagnetic field measurements with nondetects

Abstract: Exposimeters are increasingly applied in bioelectromagnetic research to determine personal radiofrequency electromagnetic field (RF-EMF) exposure. The main advantages of exposimeter measurements are their convenient handling for study participants and the large amount of personal exposure data, which can be obtained for several RF-EMF sources. However, the large proportion of measurements below the detection limit is a challenge for data analysis. With the robust ROS (regression on order statistics) method, su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
83
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 104 publications
(87 citation statements)
references
References 15 publications
3
83
1
Order By: Relevance
“…means, medians, 25 th , 75 th and 95 th percentiles) compared to the former method . Röösli et al (2008) also observed that the larger the proportion of censored data, the larger was the difference between the substitution (by LOD) and the ROS mean. The frequency-specific LODs for the exposimeter used in our study were lower compared to those employed in previous studies (EME SPY) (Bhatt et al, 2016b), which suggest that our devices were more sensitive than EME SPY.…”
Section: 1mentioning
confidence: 84%
See 1 more Smart Citation
“…means, medians, 25 th , 75 th and 95 th percentiles) compared to the former method . Röösli et al (2008) also observed that the larger the proportion of censored data, the larger was the difference between the substitution (by LOD) and the ROS mean. The frequency-specific LODs for the exposimeter used in our study were lower compared to those employed in previous studies (EME SPY) (Bhatt et al, 2016b), which suggest that our devices were more sensitive than EME SPY.…”
Section: 1mentioning
confidence: 84%
“…The performance of these methods has been evaluated using simulations on single and contaminated lognormal data and it was found that LOD/√2 substitution method provided slightly positively biased means and negatively biased 95 th percentiles, yet plausible results compared to more advanced approaches (Hewett & Ganser, 2007). Substitution methods have been used in RF-EMF personal exposure assessment elsewhere (Ibrani et al, 2016;Thomas et al, 2008;Röösli et al, 2008).…”
Section: 1mentioning
confidence: 99%
“…To take into account that a large proportion of data points were below the lower detection limit of the exposimeter, arithmetic mean values have been calculated for each measurement day per frequency and per environment with the robust regression on order statistics (ROS) algorithm using the statistical software R Version 3.0.1 (www.r-project.org) (Röösli et al, 2008). A full description of the analysis method can be found in Helsel (2005).…”
Section: Statistical Analysesmentioning
confidence: 99%
“…The lower were calculated using the robust regression on order statistics (ROS) algorithm (Röösli et al 2008). If less than three measurements were above the detection limit for a given area and frequency band, the arithmetic mean value was set to 0.000265 mW/m 2 (0.01 V/m).…”
Section: Statistical Analysesmentioning
confidence: 99%